The Representation of Sakinah's Meaning in the Qur'an Perspective - Jeri Saputra Jeri (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
The concept of sakinah is one of the fundamental values in the Qur’an, closely related to family life and marital relationships. Qur’an Surah Ar-Rum (30): 21 explicitly mentions sakinah as the purpose of the creation of spouses, along with mawaddah and rahmah. This study aims to examine the meaning of sakinah in this verse using Roland Barthes’ semiotic approach, which emphasizes three levels of meaning: denotation, connotation, and myth as a form of cultural meaning construction. This research employs a qualitative method with a library research design, using the Qur’an and classical as well as contemporary Qur’anic commentaries as primary sources, supported by relevant secondary literature. The findings reveal that at the denotative level, sakinah refers to tranquility and inner peace within marital life. At the connotative level, sakinah represents a harmonious and balanced relationship grounded in spiritual values. At the level of myth, sakinah is understood as an ideal construction of the Islamic family that emphasizes emotional stability, moral commitment, and social responsibility. Thus, sakinah is not merely interpreted as psychological calmness but also reflects a value system that shapes the Islamic family paradigm.